MIDI-Based Music Dynamics Learning: A Strategy to Improve Expression and Musical Sensitivity of Third Grade Elementary School Students Pedagogia - Muflikhul Khaq; Lina Ambarwati; Raudya Setya Wismoko Putri; Mita Saputri (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2026)
Music education in elementary schools plays an essential role in nurturing students’ musical sensitivity and vocal expressiveness. However, initial observations of third-grade students at Pedagogia Elementary School showed that singing activities were conducted without accompaniment or expressive guidance, resulting in flat, monotonous performances. This study investigates the effect of a Musical Instrument Digital Interface/MIDI-assisted music-dynamics learning strategy on vocal expression and musical awareness. Using a descriptive quantitative approach with a one-group pretest–posttest design, the study involved 25 third-grade students who learned dynamic markings such as forte, piano, crescendo, and decrescendo supported by MIDI tracks. Data were collected through observation sheets, vocal performance rubrics, and field notes. The findings reveal significant improvements in articulation clarity, in the accuracy of applying dynamic symbols, and in the liveliness of facial expressions. Overall, the results demonstrate that integrating MIDI technology can effectively strengthen expressive singing skills and enrich musical learning experiences in elementary education for young learners.